A retroactive spatial cue improved VSTM capacity in mild cognitive impairment and medial temporal lobe amnesia but not in healthy older adults. (October 2015) - Newsome, Rachel N.; Duarte, Audrey; Pun, Carson; Smith, Victoria M.; Ferber, Susanne; Barense, Morgan D.
Abstract: Visual short-term memory (VSTM) is a vital cognitive ability, connecting visual input with conscious awareness. VSTM performance declines with mild cognitive impairment (MCI) and medial temporal lobe (MTL) amnesia. Many studies have shown that providing a spatial retrospective cue ("retrocue") improves VSTM capacity estimates for healthy young adults. However, one study has demonstrated that older adults are unable to use a retrocue to inhibit irrelevant items from memory. It is unknown whether patients with MCI and MTL amnesia will be able to use a retrocue to benefit their memory. We administered a retrocue and a baseline (simultaneous cue, "simucue") task to young adults, older adults, MCI patients, and MTL cases. Consistent with previous findings, young adults showed a retrocue benefit, whereas healthy older adults did not. In contrast, both MCI patients and MTL cases showed a retrocue benefit – the use of a retrocue brought patient performance up to the level of age-matched controls. We speculate that the patients were able to use the spatial information from the retrocue to reduce interference and facilitate binding items to their locations. Highlights: A spatial retrocue improved VSTM capacity in MCI and MTL amnesia to the level of controls. Healthy older adults were unable to benefit from the retrocue. Patients were able to use spatial information to reduce interference and facilitate item-location binding.